Perlindungan Hak Cipta Musik di Indonesia: Kajian Yuridis terhadap Undang-Undang dan Implementasinya - Rafie Maulana Putra (PT. Hasba Edukasi Mandiri, 2026)
Music copyright is a crucial element in Indonesia's creative industry ecosystem, comprehensively regulated by Law Number 28 of 2014 on Copyright. This article conducts an in-depth legal analysis of music copyright protection, covering historical aspects, legal substance, practical challenges, and policy recommendations. Using normative and empirical approaches, this study identifies that although the legal framework has been updated, violations of music copyrights remain a major issue due to limitations in law enforcement and the impact of digital technology. Proposed solutions include strengthening supervisory institutions and public education. Keywords: music copyright, Indonesia, law, law enforcement, creative industry.